Purpose and consent enforcement in DBMS - Machado, Javam; Amora, Paulo; Praciano, Francisco D. B. S. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais Estendidos do XXXIX Simpósio Brasileiro de Bancos de Dados, 2024)
Nowadays, personal data is subject to laws and regulations that oblige data holders to ensure proper compliance with users’ consent regarding how their data should be used. Existing tools in the DBMS, like RBAC/FGAC, can accomplish some level of control over data. However, they cannot model and correctly apply the required and desired restrictions, bringing this theme to a resurgence. In this tutorial, we explore a timeline of approaches to solve purpose-based access control and compare recent works over a common baseline to assert strong and weak points and suggest new research topics on this theme.